Enduring Personality Changes after Intense Stressful Event: Case Report - Arsova, Slavica (Open Access Maced J Med Sci, 2016)
BACKGROUND: World statistical data show that a large number of individuals suffer from posttraumatic stress disorder (PTSD) after exposure to the intense traumatic event. PTSD can have a chronic course with enduring changes in the functioning of the person. CASE PRESENTATION: Here we report two adult individuals of different gender and education who were exposed to the extremely severe stressful event after which difficulties in psychological functioning developed. The first case we present is a 46-year-old man, with completed high education, divorced, father of two children, who lives with his parents, and is retired. Disorders appeared 20 years ago when he was exposed to extremely severe stressful events in war circumstances that included captivity, torture, and loss of fellow soldiers. The second case is a 50-year-old female patient, with a university degree, professor of art, married, and mother of two children of whom the son died six years ago. She suffered from disorders after the sudden injury of her son that ended with his death. CONCLUSION: Posttraumatic stress disorder after the intense stress is a risk of development enduring personality changes with serious individual and social consequences.